LIPG-mediated regulation of lipid deposition and proliferation in goat intramuscular preadipocytes involves the PPARα signaling pathway - Yinggui Wang; Lian Huang; Jiangjiang Zhu; Wenyang Zhang; Yinmei Tang; Changheng Yang; Yaqiu Lin; Yong Wang; Hua Xiang (PLoS ONE, 2025)
Endothelial lipase (LIPG), a member of the triglyceride lipase family, plays an essential role in human diseases and lipid metabolism. However, its function in goat intramuscular fat (IMF) deposition remains unclear. In this study, we investigated the role of the LIPG gene in IMF deposition by knocking down and overexpressing it in goat intramuscular preadipocytes. We successfully cloned the full-length LIPG gene, which spans 2,131 bp, including a 94 bp 5’ untranslated region (5’UTR), a 1,503 bp coding sequence (CDS), and a 534 bp 3’ untranslated region (3’UTR). Tissue expression profiles showed that LIPG is expressed in the heart, liver, spleen, Kidney, longest dorsal muscle, and small intestine tissues of goats. LIPG knockdown significantly inhibited both the proliferation of intramuscular preadipocytes and lipid deposition. Moreover, LIPG knockdown markedly decreased mRNA expression of FASN, LPL, CPT1A, CPT1B, FABP3, while increasing the mRNA expression of ATGL, ACOX1, FADS1, and ELOVL6. These findings were further corroborated through LIPG overexpression experiments. Using RNA sequencing (RNA-seq), we identified 1695 differentially expressed genes (DEGs) between the negative control (NC) and LIPG knockdown (Si-LIPG) groups, with KEGG pathway analysis revealing significant enrichment in the PPAR signaling pathway. Additionally, LIPG knockdown significantly upregulated the expression of both mRNA and protein levels of PPARα. The PPARα agonist WY14643 was able to reverse the enhanced lipid deposition induced by LIPG overexpression. In conclusion, our study highlights a key role for LIPG in the regulation of goat intramuscular preadipocyte proliferation and lipid deposition, potentially through the PPARα signaling pathway. These findings provide new insights into the regulatory mechanisms governing IMF deposition and suggest potential strategies for improving goat meat quality.